Satire Found In The Daily Show With Trevor Noah - Ichsan, Muhammad (Universitas Muhammadiyah Sumatera Utara, 2021)
This study deal with the analysis satire in the Daily Show with Trevor Noah. The objectives of the study were to find out the types of satire, to describe how the host is used satire in the Daily Show with Trevor Noah. The data in this research was taken from the Daily Show with Trevor Noah. Descriptive qualitative method was applied to analyzed the data. Thus, in doing this research, library research was applied in analyzing the data. It took seven episodes of the Daily Show with Trevor Noah. Which were downloaded from internet. The data focused on the utterances of the host inthe Daily Show with Trevor Noah that consist of Satire. Based on the analysis, there were three types of Satire occurred in the show namely Horation satire, Juvenalian satire and Manippean satire proposed by Abrams theory. The host used irony, parody, comparison and humor in satire to criticize and satirize for the cluster of ideas and peoples behavior occurred in the Daily Show with Trevor Noah.